1946
DOI: 10.1021/ie50438a020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Volumes of Mononuclear Aromatic Hydrocarbons.

Abstract: T h e inolecular *olunies of 1-phenylalkanes and 2-pheii) 1-alkanes at any @\en fraction of the critical temperature are linear functions of the nuniber of carbon atoms. RIolecuIar\ olunies of fourteen homologous series of mononuclear aromatic h>drocarbons at 20' C. are also linear functions of the number of carbon atonis. Both of these relationships may be expressed by equations of the forni : M / d = V = a -+ bn Constants a and b are simple functions of the reduced temperature. These functions may be express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1948
1948
1949
1949

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In order to judge the reliability of an observation or to choose between badly discrepant ones, it is desirable to have a comprehensive correlation between the properties and structures of hydrocarbons. Three papers by Corbin, Alexander, and Egloff (70,71,72) have already correlated the properties of the simpler types of alkylbenzenes,-namely, the 1-and 2-phenylalkanes,-and some of the dialkylbenzenes, but less than one-seventh of the total number of known alkylbenzenes are included. In a fourth paper (73) the same authors showed the relation of boiling point to pressure for some additional alkylbenzenes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to judge the reliability of an observation or to choose between badly discrepant ones, it is desirable to have a comprehensive correlation between the properties and structures of hydrocarbons. Three papers by Corbin, Alexander, and Egloff (70,71,72) have already correlated the properties of the simpler types of alkylbenzenes,-namely, the 1-and 2-phenylalkanes,-and some of the dialkylbenzenes, but less than one-seventh of the total number of known alkylbenzenes are included. In a fourth paper (73) the same authors showed the relation of boiling point to pressure for some additional alkylbenzenes.…”
Section: Introductionmentioning
confidence: 99%
“…The boiling-point calculations of Burnop (1), Klages (20), and Kinney (17,19) can be applied to mononuclear aromatics, and correlations of boiling point, molecular volume, and molal refraction have been worked out for several homologous series by Corbin, Alexander, and Egloff (3,4,6).…”
mentioning
confidence: 99%